PENGARUH SISTEM PEMASARAN KACANG PANJANG TERHADAP PENDAPATAN PETANI DI DESA KURIPAN KECAMATAN BABAT KABUPATEN LAMONGAN - E Y. Arvianti; Mubaidi Mubaidi (BUANA SAINS, 2012)
One of the horticulture commodity able to take role in agricultural development is string bean. In Sub-Province Lamongan, centre production of string bean is District Babat, Sekaran, Laren and Kedung Pring with productivity; level 15,0 t/ha. Result of research indicate there is two, system marketing of string bean in Village Kuripan, and channel marketing I (entangle farmer, merchant mount countryside/supermarket and wholesaler), channel II (entangle farmer, compiler merchant mount supermarket and district). Executed by marketing function that is transfer function which consist of purchasing, sale and physical function (depository and transportation function, and also facility function that is market information). Efficiency marketing value at channel marketing of I (0.26%), relative lower if compared to marketing efficiency value at channel marketing of II (3.17%). It is assume channel marketing of I relative more efficient because efficiency value smaller than II channel and its marketing marjin also smaller relative